Effects of carbophos on rat testopathy following resveratrol administration: An experimental study - Cyrus Jalili; Shiva Roshankhah; Azita Faramarzi; Mohammad Reza Salahshoor (Reproductive and Developmental Medicine, 2019)
Objective: Carbophos (CAR) is an organophosphate that is most capable of producing free radicals and inducing alteration in some of the male reproductive parameters. Resveratrol (RES) is an herbal polyphenol and exerts beneficial antioxidant effects. This study aimed to evaluate the effects of RES against CAR-induced alteration in reproductive parameters of male rats. Methods: In this experimental study, 48 male rats were randomly assigned to eight groups: Group 1: Normal control (saline) group; Group 2: CAR control (250 mg/kg) group; Groups 3–5: 2, 8, and 20 mg/kg RES, respectively, groups; Groups 6–8: CAR plus 2, 8, and 20 mg/kg RES, respectively, groups. The agents were administered intraperitoneally and by gavage daily for 65 days. Sperm parameters, testis malondialdehyde (MDA) levels, total antioxidant capacity, testosterone levels, and germinal layer height were evaluated and compared among these groups. Results: No significant alterations were observed in RES groups (with different doses) compared to the normal control group (P > 0.05). The levels of all parameters except MDA (which decreased) significantly increased in the CAR plus RES (with different doses) groups compared to the CAR control group (P < 0.01). Conclusions: RES attenuates the toxic effect of CAR on some of the male reproductive parameters.